Atividade da natamicina sobre Saccharomyces cerevisiae - Dal Prá, Valéria (My University, 2022)
Natamycin is an antibiotic used as a chemical additive in industrial processes for some foods due to its antifungal potential, but its ingestion in large quantities can cause negative reactions in humans. Thus, it becomes necessary to investigate and evaluate the effective and safe concentration of natamycin in food products. This antibiotic binds irreversibly to ergosterol in the fungal cell membrane, leading to the formation of ion channels and consequently increasing cell permeability, resulting in microbial death. This study aimed to determine the inhibitory and lethal concentration, in addition to the activity of natamycin on yeast cells and possible effects on lymphocytes. For this, a strain of Saccharomyces cerevisiae (BY4741) that received treatments with natamycin at different concentrations was used to determine the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC). The Natamycin is an antibiotic used as a chemical additive in industrial processes for some foods due to its antifungal potential, but its ingestion in large quantities can cause negative reactions in humans. Thus, it becomes necessary to investigate and evaluate the effective and safe concentration of natamycin in food products. This antibiotic binds irreversibly to ergosterol in the fungal cell membrane, leading to the formation of ion channels and consequently increasing cell permeability, resulting in microbial death. This study aimed to determine the inhibitory and lethal concentration, in addition to the activity of natamycin on yeast cells and possible effects on lymphocytes. For this, a strain of Saccharomyces cerevisiae (BY4741) that received treatments with natamycin at different concentrations was used to determine the minimum inhibitory concentration (MIC) and the minimum fungicidal concentration (MFC). The fungicide effect on cell membrane integrity, intracellular esterase activity, intracellular ROS accumulation, mitochondrial membrane potential and metacaspase activity was evaluated by flow cytometry. For yeast BY4741 the MIC and CFM obtained was 1.56 mg/L and 25 mg/L of natamycin, espectively. The cell membrane integrity (viability) of the yeast showed a reduction proportional to the amount of natamycin, reaching 99% mortality at 25 mg/L. The fungicide led to an increase in intracellular ROS and an alteration in the mitochondrial membrane potential, altering the respiratory capacity. Furthermore, the increase in metacaspase indicates apoptotic death by natamycin in yeast. Natamycin did not affect animal lymphocyte cells even at high concentrations (50 mg/L). From this result it is possible to verify the efficiency on Saccharomyces cerevisiae and the possibility of its use in other foods. fungicide effect on cell membrane integrity, intracellular esterase activity, intracellular ROS accumulation, mitochondrial membrane potential and metacaspase activity was evaluated by flow cytometry. For yeast BY4741 the MIC and CFM obtained was 1.56 mg/L and 25 mg/L of natamycin, respectively. The cell membrane integrity (viability) of the yeast showed a reduction proportional to the amount of natamycin, reaching 99% mortality at 25 mg/L. The fungicide led to an increase in intracellular ROS and an alteration in the mitochondrial membrane potential, altering the respiratory capacity. Furthermore, the increase in metacaspase indicates apoptotic death by natamycin in yeast. Natamycin did not affect animal lymphocyte cells even at high concentrations (50 mg/L). From this result it is possible to verify the efficiency on Saccharomyces cerevisiae and the possibility of its use in other foods. [resumo fornecido pelo autor]
A natamicina é um antibiótico utilizado na forma de aditivo químico em processos industriais de alguns alimentos devido ao seu potencial antifúngico, porém a sua ingestão em grandes quantidades pode causar reações negativas no homem. Assim, torna-se necessário investigar e avaliar a concentração de natamicina eficaz e segura em produtos alimentícios. Este antibiótico realiza ligação irreversível ao ergosterol da membrana celular do fungo, levando à formação de canais iônicos e consequentemente aumentando da permeabilidade celular, resultando em morte microbiana. O objetivo deste estudo foi determinar a concentração inibitória e letal, além da atividade da natamicina sobre células de leveduras e possíveis efeitos em linfócitos. Para isto foi utilizada uma cepa de Saccharomyces cerevisiae (BY4741) que recebeu tratamentos com natamicina em diferentes concentrações para determinação da concentração inibitória mínima (CIM) e da concentração fungicida mínima (CFM). O efeito do fungicida sobre a integridade da membrana celular, atividade da esterase intracelular, acúmulo de ROS intracelular, potencial de membrana mitocondrial e atividade de metacaspase foi avaliado através de citometria de fluxo. Para a levedura BY4741 a CIM e CFM obtido foi de 1,56 mg/L e 25 mg/L de natamicina, respectivamente. A integridade da membrana celular (viabilidade) da levedura apresentou redução proporcional à quantidade de natamicina, chegando a 99% de mortalidade com 25 mg/L O fungicida levou ao aumento de ROS intracelular e à alteração do potencial de membrana mitocondrial, alterando a capacidade respiratória. Além disso, o aumento de metacaspase indica morte apoptótica pela natamicina em leveduras. A natamicina não apresentou efeito sobre células animais linfocitárias mesmo em concentrações elevadas (50 mg/L). A partir deste resultado é possível verificar a eficiência sobre Saccharomyces cerevisiae e a possibilidade de utilização em outros alimentos. [resumo fornecido pelo autor]
Keywords: Saccharomyces cerevisiae; Citometria de fluxo; Natamicina; Ciências da vida